Environmental Sensitivity Analysis of Oil Spills: A Case Study in Coastal Areas - Ardiansyah, Ichsan Prayoga; Liyantono, Liyantono; Effendi, Hefni; Ikrari, Karaben Ikhtiyana (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2025)
The coastal areas of Karawang Regency are at risk of being affected by oil spills originating from oil pipelines leaking. The purpose of this research is to develop an environmental sensitivity index based on the assessment standards of the National Oceanic and Atmospheric Administration, with research locations in the Karawang Coast. The results showed that the resources in the Karawang coastal area that sensitive to oil spills are shoreline type of mangrove  with a total length of 34.76 km of shoreline; consist of dense mangrove forest with an area of 173.14 ha; capture fisheries with 6,832 fishermen with a production of 9,319.38 tons/year; and aquaculture involving 5,643 fishing households with a production of 43,389.45 tons/year. The environmental sensitivity index value was concluded as very sensitive for mangrove beaches, mangrove forests in all locations and aquaculture in the Tirtajaya & Batujaya areas, while the capture fisheries and the capture aquaculture were concluded as sensitive. The environmental sensitivity index maps of the three themes indicated that the socio-economic component is the most sensitive component compared to other components. Specifically, the socio-economic components that were the most sensitive to the impact of oil contamination were aquaculture and capture fisheries areas.